Cardiogenic Shock - Bagaswoto, H. P.; Juzar, D. A.; Habib, F.; Bramantyo, Y. S.; Sanggula, P. N. P. P.; Widiastuti, A. Z. (Jurnal Kardiologi Indonesia, 2025)
In “Cardiogenic Shock” (Indonesian Journal of Cardiology, 43(2), 90-9. https://doi.org/10.30701/ijc.1505), there are an errors noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1505. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. An error also appears in the affiliations section. In the original article, the affiliations were incorrectly listed as:[1] Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada - Sardjito General Hospital, Yogyakarta[2] Faculty of Medicine, Universitas Indonesia - National Cardiovascular Center Harapan Kita, Jakarta[3] Faculty of Medicine, Universitas Sumatera Utara - Adam Malik General Hospital, Medan[4] Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta The affiliations have been corrected to:[1] Department of Cardiology and Vacular Medicine, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada - Sardjito General Hospital, Yogyakarta, Indonesia[2] Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Indonesia - National Cardiovascular Center Harapan Kita, Jakarta, Indonesia[3] Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sumatera Utara - Adam Malik General Hospital, Medan, Indonesia[4] Cardiology Research Office, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta, Indonesia The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1505